2009
DOI: 10.1126/science.1167525
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative 3D Video Microscopy of HIV Transfer Across T Cell Virological Synapses

Abstract: The spread of HIV between immune cells is greatly enhanced by cell-cell adhesions called virological synapses, although the underlying mechanisms have been unclear. With use of an infectious, fluorescent clone of HIV, we tracked the movement of Gag in live CD4 T cells and captured the direct translocation of HIV across the virological synapse. Quantitative, high-speed three-dimensional (3D) video microscopy revealed the rapid formation of micrometer-sized “buttons” containing oligomerized viral Gag protein. El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
603
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 454 publications
(627 citation statements)
references
References 26 publications
24
603
0
Order By: Relevance
“…These two modes of adhesion-induced transmission can both contribute to efficient virus cell-to-cell transmission. The here observed behavior of HIV Gag in the context of an MLV Env/receptor synapse is consistent with the observation of lateral movement of HIV to the virological synapse in T cells (13,41). The ability of HIV to utilize surface movement may also explain independence from the cytoplasmic tail of the envelope, although a dependence has also been reported (6,10).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…These two modes of adhesion-induced transmission can both contribute to efficient virus cell-to-cell transmission. The here observed behavior of HIV Gag in the context of an MLV Env/receptor synapse is consistent with the observation of lateral movement of HIV to the virological synapse in T cells (13,41). The ability of HIV to utilize surface movement may also explain independence from the cytoplasmic tail of the envelope, although a dependence has also been reported (6,10).…”
Section: Discussionsupporting
confidence: 72%
“…In the case of the human immunodeficiency virus (HIV) and the human T cell lymphoma virus these cell-cell contacts share features with immunological synapses and have been designated infectious or virological synapses (13,14,19,29,41). Using the murine leukemia virus (MLV) as a model system, we demonstrated that the interaction between the viral Env glycoprotein (Env), expressed on the infected cell and the viral receptor, expressed on the uninfected target cell, leads to the establishment of cell-cell contacts (32,45).…”
mentioning
confidence: 99%
“…E.g. it is now well known that the human immunodeficiency virus (HIV) can spread very efficiently from an infected T cell to an uninfected T cell through direct cell-cell contact [1][2][3][4]. Imaging this process in living cells is, however, very tedious and time-consuming due to the fact that T cells are non-adherent and only a fraction of cells will contain the virus [4,5].…”
Section: Biophotonicsmentioning
confidence: 99%
“…In a separate report in this issue of JASN, Rosolowsky et al 8 did find a secular trend in a similar cohort of patients with type 1 diabetes from the Joslin Clinic. They found a rate of ESRD that was virtually identical to that of the FinnDiane cohort and likewise observed that progression to ESRD was the predominant outcome among their patients with type 1 diabetes and macroalbuminuria.…”
mentioning
confidence: 98%
“…7,8 Cell-to-cell transmission is described mostly between infected T cells or virus-laden antigen-presenting cells and uninfected T cells. This interaction at the site of cell-to-cell contact is called a virologic synapse with polarized T cells forming a protrusion called uropod, which mediates contact with the other cell.…”
mentioning
confidence: 99%